Potensi Galur-Galur Padi Rawa Pasang Surut Menunjang Ketahanan Pangan - Rosmini Humairi; Izhar Khairullah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2000)
The advance yield trial was conducted at potential tidal swampland at Inlittra Handil Manarap. South Kalimantan in dry season of 2000. Nine advanced lines, designationly IR53709-36-10-2; B729Id-Sm-Tb-5; BW 307-6; B10278b-Mr-3-3-1; B10179b-Mr-1-4-2; BI0278b-Mr-1-4-2; B10277b-Mr-1-4-3; TOX3118-6-E2-3-2; BIOI79b-Mr-1- 4-1 and Kapuas variety used as a check variety. The trial was arranged in randomized completely block design with three replications. The trial showed that there were five advanced lines which their yield were higher than Kapuas, i.e. B7291d-Sm-Tb-5; BW307-6; BI0278b-Mr-3-3-1; BIOI79b-Mr-I-4-2; BIOI 79b-Mr-I-4-1. The yield of the five lines were 2.47; 2.42; 2.45; 2.50; and 2.29 t/ha, respectively while yield of Kapuas variety was only 2.20 t/ha. Percentage of yield increasing of these lines, if compared by Kapuas, were 1.27; 10; 11.36; 13.64; 4.09 % respectively. Key words: Rice, Tidal swamp, field